ФОРМУВАННЯ КОМУНІКАТИВНОЇ КУЛЬТУРИ МАЙБУТНІХ ПЕДАГОГІВ ЗАСОБОМ ВИКОРИСТАННЯ АКТИВНИХ МЕТОДІВ НАВЧАННЯ В ПРОЦЕСІ ВИВЧЕННЯ НІМЕЦЬКОЇ МОВИ (Педагогіка вищої та середньої школи, 2010)
This article considers the problem of formation of the communicative culture of future teachers of foreign languages in the context of realization the active methods of teaching during studying the German language.